2023
DOI: 10.7554/elife.85092
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling impairs alveolar epithelial regeneration in pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) consists of fibrotic alveolar remodeling and progressive loss of pulmonary function. Genetic and experimental evidence indicate that chronic alveolar injury and failure to properly repair the respiratory epithelium are intrinsic to IPF pathogenesis. Loss of alveolar type 2 (AT2) stem cells or mutations that either impair their self-renewal and/or impair their differentiation into AT1 cells can serve as a trigger of pulmonary fibrosis. Recent reports indicate increased YAP ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Indeed, Alpelisib and AZD6482 did not reach hit criteria but increased HiBiT values (1.87- and 1.65-fold change vs DMSO, respectively), which helped identify the involvement of PI3K/AKT signaling in AT1 cell differentiation. Wnt signaling inhibitor and YAP/TAZ signaling activator were expected to be hits in the compound screening since we previously reported that XAV939, a suppressor of the canonical Wnt signaling via inhibition of tankyrase, promoted iAT1 cell differentiation from iAT2 cells in FD-AOs, and YAP/TAZ signaling is essential in AT1 cell differentiation ( DiGiovanni et al., 2023 ; Gokey et al., 2021 ; Kanagaki et al., 2021 ; LaCanna et al., 2019 ; Liu et al., 2016 ; Nguyen et al., 2021 ; Warren et al., 2023 ). In the present study, we removed CHIR99021, which activates the canonical Wnt signaling via inhibition of GSK3β, from the medium before screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Alpelisib and AZD6482 did not reach hit criteria but increased HiBiT values (1.87- and 1.65-fold change vs DMSO, respectively), which helped identify the involvement of PI3K/AKT signaling in AT1 cell differentiation. Wnt signaling inhibitor and YAP/TAZ signaling activator were expected to be hits in the compound screening since we previously reported that XAV939, a suppressor of the canonical Wnt signaling via inhibition of tankyrase, promoted iAT1 cell differentiation from iAT2 cells in FD-AOs, and YAP/TAZ signaling is essential in AT1 cell differentiation ( DiGiovanni et al., 2023 ; Gokey et al., 2021 ; Kanagaki et al., 2021 ; LaCanna et al., 2019 ; Liu et al., 2016 ; Nguyen et al., 2021 ; Warren et al., 2023 ). In the present study, we removed CHIR99021, which activates the canonical Wnt signaling via inhibition of GSK3β, from the medium before screening.…”
Section: Discussionmentioning
confidence: 99%
“…Signals that regulate the differentiation of AT2-to-AT1 cells have been explored. Among them, the activation of yes-associated protein and the transcriptional coactivator with PDZ-binding motif (YAP/TAZ) signaling is essential for AT1 cell differentiation ( DiGiovanni et al., 2023 ; Gokey et al., 2021 ; LaCanna et al., 2019 ; Liu et al., 2016 ; Nguyen et al., 2021 ; Penkala et al., 2021 ; Warren et al., 2023 ). Other signals such as Notch, transforming growth factor β (TGF-β), Wnt, and p53 are also involved in AT2-to-AT1 cell differentiation ( Finn et al., 2019 ; Frank et al., 2016 ; Kaiser et al., 2023 ; Kanagaki et al., 2021 ; Zhao et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Hippo signaling pathway is an important participant in lung cellular homeostasis and is described in detail in both healthy and pathological states [ 11 13 ]. The transcriptional coactivators of the Hippo pathway are YAP and its homolog TAZ; they regulate target gene expression and, as a consequence, proliferation, differentiation, and cell viabilty.…”
Section: Introductionmentioning
confidence: 99%
“…The process is thought to be an accumulation of extracellular matrix (ECM) over the long term. Permanent inhibition of oxygen transfer occurs due to this accumulation, which causes shortness of breath 1–5 …”
Section: Introductionmentioning
confidence: 99%
“…Permanent inhibition of oxygen transfer occurs due to this accumulation, which causes shortness of breath. [1][2][3][4][5] The precise causes of histopathological changes in IPF remain unknown. IPF is associated with various risk factors like smoking, infections, pollutants, genetics, and drugs.…”
Section: Introductionmentioning
confidence: 99%